Asuhan Keperawatan Medikal Bedah Pada Pasien Dengan Tuberculosis Paru (TB Paru) Di Ruang Paru RSUP Dr. M. Djamil Padang - Nazla Defri Kirana; Debby Silvia Dewi; Linda Marni; Hilma Yessi (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
According to World Health Organization data, Indonesia ranks second in tuberculosis case globally. Hospital records at Doctor Mohammad Djamil Central General Hospital Padang registered two hundred and fifty-eight cases of pulmonary tuberculosis in two thousand and twenty-five, requiring serious management. This study aims to implement comprehensive medical surgical nursing care for a patient with pulmonary tuberculosis. The research method used was a six-day descriptive case study conducted on Mr. A in a pulmonary isolation ward. Assessment results showed that the patient experienced shortness of breath, a productive cough with yellowish-green sputum mixed with blood, nausea, and weight loss. The primary nursing problems included ineffective airway clearance, impaired gas exchange, ineffective breathing pattern, nutritional deficit, risk of infection, and knowledge deficit. Interventions performed included airway management, respiratory monitoring, ventilatory support via high flow nasal cannula, and health education. The final evaluation indicated that all nursing problems were completely resolved. This case study suggests the importance of optimizing health education for patients and families to maintain treatment compliance and prevent transmission within the home environment.